Role of Family in Preservation and Transmission of Ethnic Culture in Udmurts of Republic of Tatarstan in 21st Century - I. L. Pozdeev (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The role of the family institution is examined in the preservation and transmission of ethnic culture of the local group of the Udmurts in the Republic of Tatarstan at the present stage in the conditions of active environment of different ethnicity and confession. The source basis of the article was the materials of ethnographic expeditions and sociological research data collected in 2003 and 2012-2013 among the Udmurts living in the Kukmor district of the Republic of Tatarstan and Naberezhnye Chelny. The author comes to the conclusion that to preserve their own identity the Udmurts of Tatarstan mobilize traditional culture, actualize ethnic and linguistic identity, relations within the ethnic group. Ethnic stereotypes, behavioral practices of the Udmurts of the Republic of Tatarstan were formed largely under the influence of the Turkic component, so adaptation to social reality makes local Udmurts to be as active as the Tatars, to develop mechanisms for preserving their cultural identity, not the least of which is the respect for their ethnic culture and awareness of its value. It is revealed that the most important factors in the reproduction of ethnic culture in zavyatskiye Udmurts are living in a predominantly Udmurt environment, a large proportion of mono-national and multi-generational families, search and constant reproduction of cultural markers in the Udmurt material and spiritual culture, the use of the native language in communication, teaching their language in schools.